Defect-type AlOx nanointerface boosting layered Mn-based oxide cathode for wide-temperature sodium-ion battery. Issue 45 (7th November 2022) - Ma, Zelin; Xu, Hanxue; Liu, Yunxuan; Zhang, Qian; Wang, Mengtong; Lin, Yuchen; Li, Zhuo; He, Xuexia; Sun, Jie; Jiang, Ruibin; Lei, Zhibin; Li, Qi; et al.
Abstract : A defect-type AlO x nanointerface containing Al 2+ has been constructed on the surface of NaMn0.6 Al0.4 O2 by surface segregation and reconstruction, which exhibits excellent Na-storage performance as the cathode of SIBs over a wide temperature range. Abstract : The O3-type layered Mn-based oxide has been considered as one of the most promising cathodes for high-performance and large-scale sodium-ion batteries due to its highly reversible capacity, easy mass production, low-toxic elemental content etc. However, the fragile interface induced by air sensitivity, potential dissolution of manganese ions in electrolytes, and low electric conductivity in this cathode often cause severe degradation of the layered structure and rapid fading of reversible capacity at room temperature, and even more so in other temperature ranges. Herein, a defective Al(II, III)O x nanointerface has uniformly been coated on the surface of an O′3-NaMn0.6 Al0.4 O2 (NMA) cathode by a one-step solid calcination with surface segregation and reconstruction from substituted Al-enrichment. This amorphous AlO x overlayer possesses abundant oxygen vacancies induced by the generation of Al 2+ and exhibits ultrahigh conductivity and stability, which enable the NMA@AlO x cathode to deliver a high discharge capacity of 155 mA h g −1, a highly enhanced rate capability and outstanding cycling performance at room temperature. Furthermore, NMA@AlO x also continues to exhibit highly effective Na-storage behaviors with small fluctuations in a wide temperature range from −20 to 60 °C. This design could provide a promising route to broaden the applications of sensitive electrode materials for high-performance and wide-temperature Na-storage devices.